Cross-language lexical priming in English-dominant bilingual Singaporeans - Chay, Zhane Tong (Nanyang Technological University, 2024)
The investigation of cross-language mental representations in bilinguals has been a longstanding focus in literature. Employing lexical priming as a methodological tool, this study delves into this issue with English-dominant bilinguals in Singapore. Due to the linguistic background of Singapore, English-Mandarin Chinese bilinguals have varying levels of proficiencies in both languages, and language balance tends to favour English. Bilingual balance, reflecting this imbalance, was computed to explore its potential influence. The study involved 42 English-dominant bilinguals in Singapore, examining cross-language and within-language semantic priming in a category verification task. Results indicated evidence of semantic priming across and within languages. Notably, cross-language priming effects were evident only when the prime was in English, the dominant language, and were unaffected by bilingual balance. These findings underscore the interconnectedness of mental lexicons across English and Mandarin Chinese in Singaporean bilinguals. However, given the complex nature of bilingual language processing, further investigation is needed to elucidate the mechanisms underlying cross-linguistic priming effects. Future research could extend these inquiries to bilinguals with diverse proficiency levels, offering deeper insights into bilingual language processing and representation.